EVALUATION OF THE APPLICATION TECHNOLOGY ACCEPTANCE MODEL 3 IN DIGITAL LIBRARY SYSTEM - Bambang, Silvi Agustanti; Winarno, Wing Wahyu; Nasiri, Asro (STKIP PGRI Tulungagung, 2025)
This study aims to analyze the acceptance of the digital library system at the University of Muhammadiyah Palangkaraya using the Technology Acceptance Model (TAM) approach. Primary data were collected through an online questionnaire distributed to over 125 respondents, with 117 completing the survey. Data analysis was conducted using Structural Equation Modeling (SEM) with SmartPLS software, following the previously outlined SEM analysis stages. Measurement model evaluation included convergent validity, discriminant validity, and reliability using the Partial Least Squares (PLS) Algorithm. The results revealed that Behavioral Intention* (BI) does not significantly influence Use Behavior (UB). In contrast, Perceived Usefulness (PU) significantly impacts BI. Additionally, Perceived Ease of Use (PEOU) significantly affects both PU and BI. The factor Image (IMG) also contributes to PU, while Job Relevance (REL) influences PU moderated by Output Quality (OUT). Result Demonstrability (RES) affects PU, and Computer Self-Efficacy (CSE) impacts PEOU. Factors such as Computer Playfulness (CPLAY), Perceived Enjoyment (JOY), and Objective Usability (OU) also affect PEOU, with their effects moderated by Experience (EXP). This study provides insights into the factors influencing the acceptance of digital library systems and can serve as a foundation for future system improvements.